DIGITAL GAME PROJECT FOR TEACHING ENGLISH FOR YOUNG LEARNERS (TEYL) - Adisti, Aprilian Ria (Journal of English Teaching and Learning Issues, 2018)
Teaching English for Young Learners (TEYL) can be integrated with the advancement of Information and Communication Technology (ICT) to raise students’ potential in learning. The use of digital game as a tool and medium has potential to facilitate students in learning English. When this colaboration used thoughtfully, it brings excellent results for improving students’ motivation in learning English. This study is a qualitative research and uses Research and Development (R & D) method which gives contribution as the alternative way to develop innovative interactive material in teaching English for Young Learners (TEYL).The result of this research is producing an education computer game for first graders of elementary schools. The education game provide interesting pictures that is completed by English dubbing therefore it attracts students to learn English